2017
DOI: 10.1080/17518423.2017.1289272
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of clinical and psychometric properties of infant oral motor feeding assessments

Abstract: Findings from this systematic review demonstrate clinical usefulness of the tools based on their assessment properties, however additional studies are needed to further establish their psychometric soundness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…A review of the literature confirmed that there is a lack of available tools to assess neonatal feeding that have adequate psychometrics and adjust scoring based on developmental changes across PMA (25). The NEO Assessment was developed by outlining key components important for feeding success.…”
Section: Methodsmentioning
confidence: 99%
“…A review of the literature confirmed that there is a lack of available tools to assess neonatal feeding that have adequate psychometrics and adjust scoring based on developmental changes across PMA (25). The NEO Assessment was developed by outlining key components important for feeding success.…”
Section: Methodsmentioning
confidence: 99%
“…feeding, and it is the most investigated for psychometric qualities (Bickell et al, 2018). As a result of its established validity, the Neonatal Eating Outcome Assessment offers an alternative standardized feeding tool, with the additional benefit of being an assessment that can gauge normal versus abnormal feeding performance across PMA with good psychometric properties.…”
Section: Discussionmentioning
confidence: 99%
“…A purpose-built assessment form (attached in Supplementary Materials) was developed as there was no available standardized assessment that met the study needs [26][27][28][29]. The assessment form was developed to incorporate assessment measures/parameters typically completed during an in-person infant feeding assessment [30][31][32][33][34][35][36].…”
Section: The Assessment Formmentioning
confidence: 99%